PENGARUH POLA ASUH ORANG TUA TERHADAP EMPATI SISWA KELAS VIII SMPN 174 JAKARTA - Nanda Rahmi Mulya; Fitniwilis Fitniwilis (Jurnal Ilmiah Global Education, 2023)
Parents' treatment of children will affect children's attitudes and behavior. One of the efforts made to form good character is with parental assistance in the form of parenting. Parents should prepare with knowledge to find the right parenting style in educating children. In his theory, Harlock states that there are three types of parenting patterns, namely democratic, authoritarian and permissive parenting. Providing the right parenting style for children can optimize children's growth and development. All of this is certainly inseparable from the role of parents, because children's behavior is a reflection of parental care, all behavior is no exception to empathetic behavior which is the result of the learning process from the environment, both directly and indirectly. This research is motivated by the problems found at SMPN 174 Jakarta while conducting PLP 2 activities for 2 months. The problem found by researchers is that the empathy of students at SMPN 174 Jakarta is quite low because there is a mismatch in the parenting patterns given by parents to their children. This study was conducted with the aim of knowing the effect of parenting on empathy. The approach used in this research is a quantitative approach. The type of research used is correlational. Data collection techniques were carried out using questionnaire distribution techniques. The population used is students in class VIII D, E F, SMPN 174 Jakarta, each class totaling 10 people and using the Simple Random Sampling technique. The results showed that based on the results obtained after conducting a simple linear analysis, the sig. value amounted to 0.149, which is based on the interpretation guidelines if the Significance value> 0.05 then there is no influence between parental parenting on student empathy.